Improving English Vocabulary through Picture Games at the Elementary School - Ruhana (Asshika: Journal of English Language Teaching and Learning, 2023)
The objective of the study was to enhance English vocabulary acquisition in elementary school students by utilising visual games. The study aimed to assess the influence of utilising graphic games on enhancing comprehension and memory of English vocabulary among elementary school students. Data is gathered via vocabulary assessments conducted before and during the integration of the visual game, as well as through observations of student reactions during educational tasks. Data analysis employs both descriptive and inferential statistical methodologies. The research findings are anticipated to enhance the development of efficacious pedagogical approaches for enhancing English vocabulary acquisition in elementary school.